Exercise testing in healthy haemodialysis patients - Milne, Frank John (Department of Paediatrics and Child Health, 2017)
1. Little work has been done on the response of regular haemodialysis patients to dynamic exercise. A systematic study of exercise capacity and the underlying mechanisms is of particular importance because these patients are encouraged to return to as normal a way of life as possible. Accordingly, a select group of healthy young male patients and a group of older males have been studied during submaximal cycling. The young male patients were compared to a closely matched sedentary control group. The 17 subjects discussed represent the fittest of 40 patients tested. 2. In both groups there was decreased work capacity associated with disproportionate tachycardia, which was not obvious at rest. Blood pressure was measured with a sphygmomanometer. During exercise there was a striking rise in the systolic blood pressure in about half the patients from currently acceptable resting levels. This occurred in the absence of any clinical circulatory overload. Mild hyperventilation and disproportionate lactic acidosis was seen towards peak exercise, probably because, in spite of the decreased work capacity, the patients were much closer to their maximum performance. However, the limiting factors were clearly circulatory and not respiratory. 3. A number of the younger male patients were more intensively studied to determine why some remained relatively 'normotensive' during exercise while others developed systolic hypertension. Total blood volume, total body water and plasma renin activity were measured at rest. It was found that the 'normotensive' patients had normal body volumes and normal to high plasma renin activity, while the hypertensive subgroup had increased volumes and normal to low plasma renin activity. Thus, in these patients the blood pressure responses to exercise were largely volume dependent, albeit at a subclinical level. 4. Cardiac output was measured at rest and during exercise. All patients developed a variable hyperkinetic circulation during exercise which was not apparent at rest. The patients were all anaemic and (xi) their cardiac output response was very like that described in patients with anaemia unassociated with renal disease. However, some patients with striking anaemia developed a less hyperkinetic circulation than others who were not so anaemic. When the body volume and the blood pressure response on exercise were considered, those patients who were normovolaemic and 'normotensive' developed a hyperkinetic circulation on exercise appropriate to their degree of anaemia. Those with subclinical volume overload and a hypertensive response to exercise developed a much less striking hyperkinetic circulation, suggesting that the blood pressure and volume excess was depressing the anticipated cardiac output response to their underlying anaemia. 5. One patient with an arteriovenous shunt was studied twice, initially when hypervolaemic with a haemoglobin of 9,1gm/100 ml and again after ultrafiltration when he was normovolaemic but his haemoglobin had risen to 12,5 gm/100 ml. On the first occasion his cardiac output response was moderately hyperkinetic but he developed increasing hypertension with a high calculated total peripheral resistance. On the second occasion his cardiac output response fell within the normal range, his blood pressure was lower but not normal and his calculated total peripheral resistance was even higher than before. Thus, the blood pressure of these volume dependent patients is due to a high total peripheral resistance, but may not simply be on the basis of 'waterlogging' of the peripheral vasculature. Some other factor, such as structural thickening, must be considered. 6. It is suggested that the combination of tachycardia and hypertension which develop on mild exertion and which may not be obvious at rest, is the most potent cause of the increased cardiovascular mortality seen in dialysis patients. Simple exercise testing will reveal those with subclinical volume overload who are most at risk. It was striking that in the two groups tested those who developed striking hypertension on exercise were usually older, between 35 and 50 years. This accelerated aging of their vascular tree would correspond with recent data showing that dialysis mortality increases with age, and is about a decade earlier than in the general population. It is suggested that a more aggressive policy be adopted towards blood pressure fluctuations and that the resting blood pressure should be kept below 140/90 mm Hg at all times, if necessary by complementing ultrafiltration with drug therapy and/or bilateral nephrectomy at an early stage. 7. Thus simple exercise testing with blood pressure recordings not only serves as a yardstick of physical rehabilitation and long-term follow-up, but may also reveal or magnify abnormalities not obvious at rest.